The origin of genetic diversity of indigenous cockfighting chickens of Pakistan by analyzing the mtDNA - Sajid Mahmood; Mian Sayed Khan; Zaib Ullah; Raman Akinyanju Lawal; Olivier Hanotte (Heliyon, 2024)
In Pakistan, the origin of the indigenous cockfighting chicken (ICC) or gamecock population is unknown. However, it is speculated that this might have been associated with domestication, an event linked to recreational, entertainment (cockfighting), religious or ornamental activities. This study aims to understand the origin and genetic diversity of the ICC population in Pakistan.A total of 185 ICC population and 10 captive Indian red junglefowl (Gallus gallus murghi) were analyzed for genetic diversity indices and phylogenetic reconstruction using a 397 bp of mtDNA D-loop region.It is reported that a total of 43 haplotypes from 38 polymorphic nucleotide sites. The haplotype and nucleotide diversity are also estimated in the range of 0.643–0.909, and 0.00585–0.01575, respectively. The total genetic diversity within the population was 91.52%. Four mitochondrial haplogroups A, B, C and D were identified by median-joining network analysis, two of them have high percentages, haplogroup D (81.6%) and A (15.1%). Phylogenetic analysis showed that the ICC population of Pakistan and Gallus gallus murghi shared haplogroup D. The results of this study showed that sub-haplogroup D17a05, has significantly high haplotype diversity and percentage as compared to previously published studies, this indicated that Pakistan might be one of the centres of domestication for chicken, as it is considered that Southeast Asia is the centre of domestication. Frequencies of Haplogroup A also indicate South-North indices. This research work showed that the indigenous cockfighting chicken population of Pakistan is genetically introgressed from Gallus gallus murghi, and significant variations could be attributed to the underlying differences in the geographics, selection pressures, introgression, and regional practices; and multiple origins of cockfighting chickens’ populations around the world which reflected the past trading routes between human communities and civilizations.